Research ethics in applied economics a practical guide - Josephson, Anna; Michler, Jeffrey D. (Abingdon, Oxon Routledge, 2024)
Research Ethics in Applied Economics Emphasizing the new challenges posed by the data science revolution, digital media, and changing standards, Research Ethics in Applied Economics examines the ethical issues faced by the applied economics researcher at each stage of the research process. The first section of the book considers project development, including issues of project management, selection bias in asking research questions, and political incentives in the development and funding of research ideas. The second section addresses data collection and analysis, discussing concerns about participant rights, data falsification, data management, specification search, p-hacking, and replicability. The final section focuses on sharing results with academic audiences and beyond, with an emphasis on self-plagiarism, self-promotion, and the importance of achieving policy impact. The discussion and related recommendations highlight emergent issues in research ethics. Featuring case studies from experienced researchers on how they address ethical issues, this book provides practical guidance to both students and experienced practitioners seeking to navigate ethical issues in their applied economics research"--
Contents: I Introduction - Research Ethics for the Applied Economist - - II Developing Research - Idea Development - - Project Development - - III Doing Research - Data Collection - - Data Management - - Data Analysis - - IV Sharing Research - Academic Research Dissemination - - Dissemination Beyond the Academy - - V Conclusion - On Being an Ethical Applied Economist.
Includes bibliographical references and index.
Keywords: Economics -- Moral and ethical aspects; Economics -- Study and teaching